2020
DOI: 10.1520/jte20180251
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation on Cyclic Shear Behavior of Geomembrane–Concrete Interfaces

Abstract: A series of cyclic shear tests was conducted to reveal the cyclic shear behavior of the interfaces between three types of geomembranes (smooth geomembranes, textured geomembranes, and composite geomembranes) and no-fines concrete. Hysteresis loops and backbone curves were obtained under different vertical pressures and shear-displacement amplitudes. The test results indicate that the textured geomembrane–concrete interface presents higher cyclic friction angles than the other two interfaces. The vertical press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The results of direct shear tests at the sand-geosynthetic interface conducted by Punetha et al [ 12 ] revealed that the shearing mechanism includes interlocking and fiber stretching while sliding, indentation and plowing for sand-geomembrane interface. Cen et al [ 16 ] investigated the cyclic shear behavior of geomembrane-concrete interface and observed that the textured geomembrane-concrete interface presents higher cyclic friction angles. Anubhav and Basudhar [ 19 ] proposed a non-linear constitutive model for predicting the pre-peak and the post-peak mechanical behavior of the soil-geotextile interface, and the peak interface shear strength was found to be significantly higher for the coarse textured geotextile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of direct shear tests at the sand-geosynthetic interface conducted by Punetha et al [ 12 ] revealed that the shearing mechanism includes interlocking and fiber stretching while sliding, indentation and plowing for sand-geomembrane interface. Cen et al [ 16 ] investigated the cyclic shear behavior of geomembrane-concrete interface and observed that the textured geomembrane-concrete interface presents higher cyclic friction angles. Anubhav and Basudhar [ 19 ] proposed a non-linear constitutive model for predicting the pre-peak and the post-peak mechanical behavior of the soil-geotextile interface, and the peak interface shear strength was found to be significantly higher for the coarse textured geotextile.…”
Section: Introductionmentioning
confidence: 99%
“…The shear strength mainly depends on the external load, joint roughness, shear rate, material property, and bonding state [ 11 16 , 19 22 ]. The surface morphology between HDPE and another material is an important factor in determining the integrality and service life of HDPE materials [ 23 ].…”
Section: Introductionmentioning
confidence: 99%